THE USE OF CLUSTERING TECHNIQUE TO IMPROVE STUDENTS' WRITING ABILITY IN RECOUNT TEXT AT GRADE X SMAN 2 SUNGAI LALA - Ririn Ariyanti; Destri Wahyuningsih (Program Studi Pendidikan Bahasa Inggris, 2026)
The purpose of this research is to find out whether the use of clustering technique can improve students' writing ability in recount text at Grade X SMAN 2 Sungai Lala. This study employed Classroom Action Research (CAR) design conducted in two cycles. The subjects were 30 students of Grade X at SMAN 2 Sungai Lala. Data were collected through writing tests, observation sheets, and field notes. The results showed that the use of clustering technique significantly improved students' writing ability in recount text. The mean score in the pre-test was 58.3, which increased to 71.6 in Cycle I and 80.4 in Cycle II. The percentage of students passing the KKM (75) also increased from 20% in the pre-test to 46.67% in Cycle I and 80% in Cycle II. These findings indicate that clustering technique is an effective pre-writing strategy that helps students generate and organize their ideas, thereby improving the quality of their recount texts in terms of content, organization, vocabulary, language use, and mechanics.